REKONSEPTUALISASI TEOLOGI KRISTEN DALAM KONTEKS POSTMODERNISASI DAN ERA KONTEMPORER: TINJAUAN TERHADAP TANTANGAN DAN PELUANG - Agnesia Friskila; Winarni Sugeanti, Jein Novita Sallo’, Emelda, Kristiani Datu Arrang (ADISAM PUBLISHER, 2023)
This research aims to analyze the process of reconceptualizing Christian theology in response to the challenges posed by the phenomenon of postmodernization and the dynamics of the contemporary era. Through a literature review analysis, this research examines how Christian theology can respond to epistemological, ontological, and ethical shifts occurring in postmodern society. The research encompasses two main focuses. First, it identifies fundamental changes in the paradigm of Christian theological thought as a result of postmodernization. This includes challenges to the authority of sacred scriptures, the role of ecclesiastical tradition, and theological interpretations of contemporary reality. Second, the research analyzes the opportunities emerging from the postmodern and contemporary context for the development of a more inclusive, contextual, and relevant Christian theology. This involves exploring the potential for interfaith dialogue, social ethics, and ecclesiastical ministry in meeting the spiritual and moral needs of today's society. The results of this research are expected to provide profound insights into the dynamics of reconceptualizing Christian theology in the face of complex social and cultural changes. This research also has the potential to contribute to the development of a Christian theology capable of accommodating and empowering individuals and communities in the contemporary era